HUBUNGAN KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH DI BANK BCA SYARIAH: HUBUNGAN KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH DI BANK BCA SYARIAH - Boma Jonaldy Tanjung; Irvan (Jurnal Publikasi Manajemen Informatika, 2022)
The implementation of the quality of services provided to customer satisfaction and response at BCA Syariah is examined in depth with the research method used is data collection which is directly observed by researchers with probability sampling and quantitative techniques. This research was conducted since June 2020 by working directly at Bank BCA Syariah. There is a strong relationship between service quality of 20.52 so that the level of satisfaction can increase positively and is influenced by the amount of customer service at BCA Syariah. The contribution made between the influence of service quality and customer satisfaction is 42.4%. This can have a positive impact and a big impact on BCA Syariah and the customers themselves. So that a good quality service provided by BCA Syariah to BCA Syariah customers will give a positive response and satisfaction for BCA Syariah customers. Utilizing human resources so that they are sufficiently knowledgeable and proficient in explaining a product, training can be held to help improve quality.